PELATIHAN PENGEMBANGAN KETERAMPILAN WIRAUSAHA DIGITAL BAGI SISWA SMA: STUDI KASUS SMA N 1 MUNTOK, KABUPATEN BANGKA BARAT - Fienda, Tiara Elgi; Fajar Agung Pangestu; Endraswari, Putri Mentari; Novaldi, Rifki Aditia; Prasetyo, Zanuar Barep (Universitas Mataram, 2025)
One of the highest contributors to the unemployment rate based on educational level is the high school level. The unemployment rate in West Bangka Regency is 4.77%, higher than the unemployment rate in the Bangka Belitung Islands Province of 4.63%. SMA N 1 Muntok, one of the schools in West Bangka Regency, has 62 students at risk of not continuing to college in 2024. These 62 students are at risk of becoming unemployed because high school is not designed as an educational level that prepares its graduates for specific skills. This problem needs to be addressed by providing training to students, one of which is the development of digital entrepreneurship skills. This is because high school students are not equipped with specific skills during school. This is different from Vocational High Schools (SMK), which are designed to prepare graduates for the world of work. There are three stages to implementing the training: preparation, training, and follow-up. In the training stage, the material provided discusses the use of the Canva application in designing flyers, creative videos using the CapCut application, and the use of Google Sites to create simple websites to maximize the reach of various business products. The training resulted in seven group projects: six flyer designs using Canva and one creative video using CapCut. The training objectives were successfully achieved, demonstrated by an increased understanding of the importance of utilizing various creative applications, which are highly beneficial for marketing entrepreneurial products.